A plethora of carbapenem resistance in Acinetobacter baumannii: no end to a long insidious genetic journey. (27th April 2021) - Vahhabi, Abolfazl; Hasani, Alka; Rezaee, Mohammad Ahangarzadeh; Baradaran, Behzad; Hasani, Akbar; Samadi Kafil, Hossein; Abbaszadeh, Faeze; Dehghani, Leila
Abstract : Acinetobacter baumannii, notorious for causing nosocomial infections especially in patients admitted to intensive care unit (ICU) and burn units, is best at displaying resistance to all existing antibiotic classes. Consequences of high potential for antibiotic resistance has resulted in extensive drug or even pan drug resistant A. baumannii . Carbapenems, mainly imipenem and meropenem, the last resort for the treatment of A. baumannii infections have fallen short due to the emergence of carbapenem resistant A. baumannii (CRAB). Though enzymatic degradation by production of class D β-lactamases (Oxacillinases) and class B β-lactamases (Metallo β-lactamases) is the core mechanism of carbapenem resistance in A. baumannii ; however over-expression of efflux pumps such as resistance-nodulation cell division (RND) family and variant form of porin proteins such as CarO have been implicated for CRAB inception. Transduction and outer membrane vesicles-mediated transfer play a role in carbapenemase determinants spread. Colistin, considered as the most promising antibacterial agent, nevertheless faces adverse effects flaws. Cefiderocol, eravacycline, new β-lactam antibiotics, non-β-lactam-β-lactamase inhibitors, polymyxin B-derived molecules and bacteriophages are some other new treatment options streamlined.